Aktivitas Antiviral Minyak Atsiri Jahe Merah terhadap Virus Flu Burung (ANTIVIRAL ACTIVITY OF ESSENSIAL OIL RED GINGER ON AVIAN INFLUENZA) - Tri Untari; Sitarina Widyarini; Michael Haryadi Wibowo (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2012)
The studies have reported that ginger have many activities such as antiemesis, anti-inflammatory,anti-bacterial and anti-parasites. Therefore, this study was conducted to evaluate antiviral effect of essentialred ginger oil againts Avian Influenza (AI) in ovo using hemagglutination test (HA). Avian Influenzaviruses were treated with 0,01%, 0,1% and 1% of essential red ginger oil, and then inoculated in chickenembryonated egg via allantoic sac. Allantoic fluid was harvested using for HA test . Result of this studyshows that application of 1% of essential red ginger oil results in the reduction of titer HA . Interestingly,essential oil shows antiviral activity revealed HA titre 20 whereas the titre HA AI which AI virus treatedwith 0,01% and 0,1% essential red ginger oil, the HA titer was 25. The conclution of this study proved thatessensial oil 1% of the red gingger is the best concentration as antiviral activity .